Usage of Blockchain Mechanism in Indian Public Administration - Kaleeshwari.S; Jegadeeshwaran (Formosa Journal of Computer and Information Science, 2024)
Blockchain is an advanced mechanism that allows transparent information for a business network. Normally databases in this technology are stored in blocks that are linked together in a chain. It is used as a facilitator for the process of recording transactions and tracking assets of a business network. It will help share data for a collective group. With blockchain, cloud service and transactional data from multiple sources can be easily collected, integrated, and shared. This technology concerning India presently is used by government banking institutions as well as the government storing and sharing data for a wider group. Blockchain is popular in finance, especially money and time. Recently India has made efforts to become a society with digitalized setup by building a large citizen-scale digital public infrastructure, which is a positive push for the government. The basic motive for introducing a high ended technology like blockchain is for maintaining transparency, and to increase the speed of interactions with individuals. This paper has made attempted to study the mechanism adopted by the Indian government under a blockchain and how well it has been utilized. It has also attempted to give a clear picture, of what all developments have made with blockchain and what sectors are much concentrated with blockchain